2012
DOI: 10.1073/pnas.1215899109
|View full text |Cite
|
Sign up to set email alerts
|

Transposon mutagenesis identifies genes that transform neural stem cells into glioma-initiating cells

Abstract: Neural stem cells (NSCs) are considered to be the cell of origin of glioblastoma multiforme (GBM). However, the genetic alterations that transform NSCs into glioma-initiating cells remain elusive. Using a unique transposon mutagenesis strategy that mutagenizes NSCs in culture, followed by additional rounds of mutagenesis to generate tumors in vivo, we have identified genes and signaling pathways that can transform NSCs into glioma-initiating cells. Mobilization of Sleeping Beauty transposons in NSCs induced th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
51
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
3
1

Relationship

3
5

Authors

Journals

citations
Cited by 64 publications
(51 citation statements)
references
References 58 publications
0
51
0
Order By: Relevance
“…Insertional inactivation of ZNF326 has also been associated with the immortalization of astroglial-like neural stem cells in SB mutagenesis studies (22). Moreover, in embryonic stem cells, ZNF326 has been shown to form complexes with NANOG and SOX2 and play an important role in stem cell self-renewal (30), suggesting that ZNF326 might also function in CSC self-renewal.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Insertional inactivation of ZNF326 has also been associated with the immortalization of astroglial-like neural stem cells in SB mutagenesis studies (22). Moreover, in embryonic stem cells, ZNF326 has been shown to form complexes with NANOG and SOX2 and play an important role in stem cell self-renewal (30), suggesting that ZNF326 might also function in CSC self-renewal.…”
Section: Discussionmentioning
confidence: 99%
“…ZNF326 regulates the expression of multiple genes in the CSC pathway Interestingly, ZNF326 was also identified in a transposon screen that identified genes, which can promote the immortalization of atroglial-like cells (22). Likewise, other studies in embryonic stem cells have shown that ZNF326 forms complexes with Nanog-Sox2, which plays an important role in stem cell selfrenewal (30).…”
Section: Znf326 Is a Ts Gene In Tnbcmentioning
confidence: 99%
See 1 more Smart Citation
“…Transposon-based insertional mutagenesis is useful as it allows for an unbiased forward genetic screen for cancer genes in mice (3,4), thereby providing a functional readout to complement cancer genome-sequencing studies. We used transposon mutagenesis to better understand the genes and pathways that are able to transform neural stem cells (NSC) into glioma-initiating cells (5), and identified La-related protein 4b (Larp4b) as a candidate tumor-suppressor gene in glioblastoma.…”
Section: Introductionmentioning
confidence: 99%
“…cells (25). This versatility and high relevance to human cancers makes SB an invaluable tool for cancer gene identification in mice.…”
mentioning
confidence: 99%